A Literature Study: How Digital Advertisements Communicate with Children - Darmawan, Levitasari (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
Internet provides a lot of space for advertisers to show various information related to commercial products and services. Both through websites and applications, currently very many advertisements appear and even annoy internet users. Internet users who also come from various circles have begun to demand deep boundaries to avoid information and content that are not suitable for certain groups. Where in this study are children, who are very familiar with the use of digital media. This study analyzes the attitude of the industry as an advertising producer, the government in making rules and regulations, and the role of society in the development of digital media that is fast and accessible, especially for children who are very close to digital media every day. Using the Systematic Literature Review (SLR) method, this study wants to answer and provide views and developments of an advertisement that can communicate with users below, namely children and adolescents, as well as boundaries that continue to develop following the development of technology and digital media.